Pharmaceutical Care Practice in Community and Institutional Drug Retail Outlets of Gondar Town, North West Ethiopia - Mohammed B Ayalew MPharm; Lidiya Solomon BPharm; Solomon Abay BPharm (SAGE Publishing, 2019)
Background Pharmaceutical care (PC) practice in Ethiopia is not well developed and is at its infant stage. As a result, very little is known about the level of involvement of pharmacy professionals in PC activities. Objective The aim of this study was to assess PC practice at drug retail outlets (DROs) of Gondar town and to identify factors associated with it. Method A cross-sectional study was conducted on 150 pharmacy professionals working in 55 DROs located in Gondar town, Northwest Ethiopia. Data on sociodemographic characteristics of respondents, their involvement in PC activities, handling of drug-related problems (DRPs), and consultation with colleagues and other health-care providers were collected and analyzed using statistical package for social sciences (SPSS) version 21. Results Majority of study participants were degree holders in pharmacy (68.7%) and work in community DROs (78%). Over half of the respondents (56.5%) were found to practice good PC, asking at least 3 of their last 5 patients what the goal of their drug therapy was. Nearly a quarter (24%) of pharmacy professionals did not document the desired therapeutic objectives for all the 5 patients they served. Handling of DRPs is poor for majority (76%) of the pharmacy professionals. Respondents working in the community DROs and diploma holders are poorly involved in PC activities. Age < 30 years, male sex, and working in the community DROs are significantly associated with poorer relation with colleague and other health-care providers. Conclusions Pharmacy professionals working in DROs of Gondar town have little involvement in the provision of PC. Especially, their handling of DRPs is very poor. The level of involvement of pharmacy professionals on some types of PC services was significantly associated with their sex, age, working site, and level of education.